The contributions of cultural tourists to the sustainability of destinations: the case of Spain - Andrés Artal Tur; Marina Villena Navarro (Revista CIDOB d'Afers Internacionals, 2016)
Because of the particular characteristics of those who engage in cultural tourism, it is an activity that can contribute to increasing the sustainability of destinations. This article seeks to broaden knowledge in this field in the case of Spain. With this aim, models of probability are applied (probit models) to a sample of international tourists to analyse the factors that improve the chances of them being cultural tourists in Spain in a period of analysis that corresponds to 2013. The results of the research allow recommendations to be made for a tourism policy in the cultural field that has a vision of the future.